2-hydroxyglutarate rides the cancer-immunity cycle - Foskolou, Iosifina; Bunse, Lukas; Van den Bossche, Jan (Current opinion in biotechnology, 2023)
2-hydroxyglutarate (2HG) is a biproduct of the Krebs cycle, which exists in a D- and L- enantiomer and is structurally similar to α-ketoglutarate. Both 2HG enantiomers have been described to accumulate in diverse cancer and immune cells and can influence cell fate and function. While D-2HG was originally considered as an ‘oncometabolite’ that aberrantly builds up in certain cancers, it is becoming clear that it also physiologically accumulates in immune cells and regulates immune function. Conversely, L-2HG is considered as an ‘immunometabolite’ due to its induction and regulatory function in T cells, but it can also be induced in certain cancers. Here, the authors review the effects of both 2HG enantiomers on immune cells within the tumor microenvironment.
Online verfügbar: 27. Juli 2023
Gesehen am 19.10.2023